PENGEMBANGAN E-BOOK SEBAGAI SUMBER BELAJAR PENDIDIKAN PANCASILA SISWA KELAS IX SMPN 3 KEDUNGWARU - Kurnia Sari, Yuliana; Eva Trisnantari, Hikmah; Listya Purnamasari, Nurna (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The research on the development of e-books as learning resources is motivated by the Pancasila Education learning process for Grade IX tudents at SMPN 3 Kedungwaru, which is still dominated by conventional learning resources in the form of printed textbooks that have not utilized multimedia elements. On the other hand, although students are already familiar with technological devices, the use of such devices for learning purposes has not yet been optimized. This study aims to produce a design, describe the implementation, and test the feasibility of interactive e-books as an alternative digital learning resource for the topic Maintaining the Territorial Intergrity of the Unitary State of the Republic of Indonesia. This study employed Research and Development (R&D) method, applying the ADDIE development model which consists of five stages: Analysis, Design, Development, Implementation, and Evaluation. Data collection instruments included validation sheets for media experts, material experts, and student response questionnaires. The trail subjects in this study were 30 students of Grade IX-A at SMPN 3 Kedungwaru. The results of the study show that: (1) The e-book was designed systematically and converted innto an interactive flipbook format via the FlipHTML5 website, complete with a combination of text, visual elements, educational videos, and assessment links. (2) The implementation of the e-book ran smoothly using smartphones or laptops, during the development stage, the product was revised by converting conventional Student Worksheets into web-based quizzes on Quizizz. (3) The feasibility level of the e-book was declared highly feasible based on validation results: material experts gave a score of 81,3% (feasible criteria), and media experts gave a score of 96% (highly feasible criteria). Furthermore, student responses yielded a percentage of 87% in the limited trial and 87,4% in the field trial, both falling under the “highly feasible” criteria.